Genetics of Absence Epilepsy and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
In a large family with epilepsy studied at the University of Melbourne, Australia, FS in 18 children were inherited as autosomal dominant with 75% penetrance (GABA receptor subunit mutation on chromosome 5), and absence epilepsy in 8 required the GABA gene on chromosome 5 interacting with a possible further gene on chromosomes 10, 13, 14 and 15.